2007
DOI: 10.1080/01904160601054825
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Fertilization of Annual Ryegrass and Comparison of Soil Phosphorus Extractants

Abstract: It is unclear how much phosphorus (P) fertilizer is needed to maximize annual ryegrass (Lolium multiflorum Lam.cv. 'TAM90') forage yield and nutritive value in lower-rainfall climates. It is equally unclear which soil-P extractant is most effective when making P fertilization decisions. A 3-yr field study addressed these issues using small replicated plots during the winter months in north-central Texas. The addition of P increased yields every year of the trial, but optimum levels depended on rainfall distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Cherney and Cherney (2005) reported that P concentrations of timothy, orchardgrass, reed canarygrass, smooth brome, and tall fescue averaged 2.35, 2.87, 3.20, 3.08, and 2.78 g K kg -1 , respectively and ranged from 2.41 to 3.32 g P kg -1 depending on the year. Butler et al (2006) reported that annual ryegrass, when grown in the same environment as this study and fertilized with 0 to 48 kg P ha -1 yr -1 , had P concentrations from 1.9 to 4.0 g P kg -1 . These values are slightly greater than the values measured in the present study with tall wheatgrass.…”
Section: Phosphorus Concentration and P Removalmentioning
confidence: 54%
See 3 more Smart Citations
“…Cherney and Cherney (2005) reported that P concentrations of timothy, orchardgrass, reed canarygrass, smooth brome, and tall fescue averaged 2.35, 2.87, 3.20, 3.08, and 2.78 g K kg -1 , respectively and ranged from 2.41 to 3.32 g P kg -1 depending on the year. Butler et al (2006) reported that annual ryegrass, when grown in the same environment as this study and fertilized with 0 to 48 kg P ha -1 yr -1 , had P concentrations from 1.9 to 4.0 g P kg -1 . These values are slightly greater than the values measured in the present study with tall wheatgrass.…”
Section: Phosphorus Concentration and P Removalmentioning
confidence: 54%
“…) averaged 9770, 7970, 9707, 7881, and 9968 kg DM ha -1 , respectively (Cherney and Cherney, 2005). Butler et al, (2006) reported DM yields of annual ryegrass (Lolium multiflorum Lam.) under the same environment as this study, which ranged from 4550 to 10510 kg DM ha -1 when fertilizer rates ranged from 0 to 40 kg P ha -1 .…”
Section: Forage Dm Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, pasture mass and P concentration quickly increases with soil test P concentration to an asymptote, after which factors other than soil P availability limit yield (Edmeades et al 2006;Saunders et al 1987). Beyond the asymptote, luxury uptake of P by the plant may parallel soil test P concentration (Butler et al 2007), but it is unknown if this would translate into potential P losses in surface runoff. Water extraction of plant and soil materials have enabled the concentration of plant P in surface runoff to be estimated (e.g., McDowell and Condron 2004;Sharpley 1981).…”
Section: Introductionmentioning
confidence: 98%